A new model for environmental and economic evaluation of renewable energy systems: The case of wind turbines. (1st March 2017) - Savino, Matteo M.; Manzini, Riccardo; Della Selva, Vincenzo; Accorsi, Riccardo
Highlights: We propose a model to join environmental and economic viability for wind turbines. Economic viability can be joint to the environmental one through carbon footprint. Configurations that appears economical viable may have high environmental impacts. Carbon fibre has lower emissions and shorter pay-back as regards to glass fibre . Changing the number of wind turbines does may worsen the joint evaluation. Abstract: Both scientific community and political institutions frequently stress the crucial role of energy and renewable energy systems as a key asset for global sustainable future development. Wind energy is a relevant renewable source due to its high conversion performances, achieved particularly by large scale plants. Nevertheless, the production processes, rather than the installation one, may entail relevant energy consumption, as well as the release of CO2 and other pollutants. This study develops a model for concurrent environmental and economic viability of wind turbines under the framework of Life Cycle Assessment. A case study is developed to evaluate a set of different project alternatives for three types of wind turbines, for which different scenarios are analysed through a dedicated assessment tool. The research highlights the manufacturing phase of wind turbines as crucial in finding the concurrent economic and environmental feasibility.